Towards Cohesive National Surveys in Pakistan: A Comparative Study of DHS and PSLM - Muhammad Ibrahim; Nayab Farman; Habib ur Rehman; Mujahid Abdullah; Amna Mahnoor Cheema; Maira Aamir; Azadeh Ahmed; Ayesha Khan; Adnan Ahmad Khan (PLoS ONE, 2025)
Introduction Effective policymaking relies on high-quality data to understand social contexts, identify target populations, and evaluate interventions. In low and middle-income countries (LMICs), household surveys often fill data gaps, providing insights into social dynamics and policy impacts. In Pakistan, the Pakistan Demographic Health Survey (PDHS) and Pakistan Social and Living Standards Measurement (PSLM) are crucial sources of information. While both surveys cover health and socioeconomic indicators, their methodologies and questionnaires vary, leading to potential discrepancies in data. Methods This paper compares PDHS 2017-18, PSLM 2018-19 (provincial level) and PSLM 2019-20 (district level) using family planning and child immunization modules as examples. Similar indicators under each section are examined for differences using weighted proportion t-test. For family planning, we analyzed PDHS 2017-18 and PSLM 2018-19 because PSLM 2019-20, doesn’t have family planning section. For immunization, we analyzed PDHS 2017-18, PSLM 2018-19 and PSLM 2019-20. Results Analysis reveals high concordance in family planning indicators with differences of within two percent. Differences in the rates of BCG which is given at birth are under one percent and for the first dose of pentavalent vaccine are near one percent. However, the differences start diverging thereafter and are near nine percent for dose 3 of the pentavalent vaccine. There is high level of concordance between the results of the provincial and district PSLM surveys conducted one year apart. Conclusion We describe the differences and relative similarities of the PSLM and PDHS surveys, as means to better incorporate their evidence in policy decisions. Both PSLM and PDHS serve a slightly different niche in that PDHS provides more in depth understanding of family planning whereas PSLM connects many health and social indicators with economic measures and gives granularity at the district level. However, to enhance the confidence of policymakers in both the surveys, we describe their concordance and differences and how they may be used in policy decisions.